1995
DOI: 10.1002/jmri.1880050121
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization transfer in MR imaging

Abstract: THE MANY DIFFERENT local environments of hydrogen nuclei within tissue give rise to complicated magnetic relaxation behavior while ensuring the rich and diverse contrast seen in magnetic resonance (MR) imaging. From an operational point of view, it has proved convenient to classify the multiple environments into two basic types: a solid-like environment and a liquid-like environment. Protons in the solid-like environmentmostly associated with macromolecules-do not experience sufficiently fast rotational or tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…19 Several authors have compared methodological aspects of cw off-resonance and pulsed on-resonance techniques. [20][21][22] Hua and Hurst showed that nominally optimized versions of each of these methods provide essentially similar MT effects at a given level of applied rf power. 21 Thus, the choice between cw or pulsed MT methods is often made on the basis of experimental considerations (available hardware, ease of implementation, possible combination with localization techniques).…”
Section: Basic Theory Models Measurement Methodsmentioning
confidence: 99%
“…19 Several authors have compared methodological aspects of cw off-resonance and pulsed on-resonance techniques. [20][21][22] Hua and Hurst showed that nominally optimized versions of each of these methods provide essentially similar MT effects at a given level of applied rf power. 21 Thus, the choice between cw or pulsed MT methods is often made on the basis of experimental considerations (available hardware, ease of implementation, possible combination with localization techniques).…”
Section: Basic Theory Models Measurement Methodsmentioning
confidence: 99%
“…CW irradiation saturates the B spins more efficiently than RF bursts set apart by a delay ?llrx While the equilibrium of A and B magnetization is constantly unbalanced during CW irradiation, as compared with the CW case, higher A magnetization is established quickly during the RF-free period of the pulsed method. (2) Even at a moderate speed of exchange of r, = 0.1 s-', a B/A concentration ratio as small as f = 1/100 is sufficient to cause a detectable MT effect.…”
Section: T2 Selection For Exchanging Systemsmentioning
confidence: 98%
“…(2) Even at a moderate speed of exchange of r, = 0.1 s-', a B/A concentration ratio as small as f = 1/100 is sufficient to cause a detectable MT effect.…”
Section: T2 Selection For Exchanging Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22] We hypothesize that if the physical basis of empirically useful biexponential decay analyses is two distinct water compartments with widely disparate diffusion coefficients, then it would reasonably follow that the two compartments might have substantially different magnetization transfer ratios. [23][24][25][26] For example, within the context of an intra-vs extracellular water compartmentation model, the intracellular water molecules responsible for the 'slow' diffusion component might reasonably be expected to experience more interactions with macromolecules, intracellular organelles, etc, than those responsible for the 'fast' diffusion component within the extracellular matrix. This in turn would lead to a larger 'bound' water fraction and so an enhanced MTR for the slow vs the fast tissue water diffusion component.…”
Section: Introductionmentioning
confidence: 99%